Birthweight Extremes and Neonatal and Childhood Outcomes after Preterm Premature Rupture of Membranes - Grace, Matthew R.; Dotters-Katz, Sarah; Varner, Michael W.; Boggess, Kim; Manuck, Tracy A. (American Journal of Perinatology, 2016)
Objective To determine the association between birthweight extremes and risk of adverse neonatal and childhood outcomes following preterm premature rupture of membranes (PPROM).Study Design This is a secondary analysis of data from the Beneficial Effects of Antenatal Magnesium Sulfate Trial. Women with nonanomalous singletons and PPROM delivering ≥24.0 weeks were included. Birthweight was classified as small for gestational age (SGA), appropriate for gestational age (AGA), or large for gestational age (LGA). Composite severe neonatal morbidity and childhood outcomes at age 2, were compared between these groups.Results One thousand five hundred and ninety-eight infants were included (58 SGA, 1,354 AGA, and 186 LGA). There was an inverse relationship between birthweight and rate of composite major neonatal morbidity (55.2% of SGA, 31.5% of AGA, 18.3% of LGA, p < 0.001). Former-SGA children were more likely to be diagnosed with major composite childhood morbidity at age 2 (25.9% of SGA, 8.3% of AGA, 5.9% of LGA, p < 0.001). In multivariate models, LGA infants had improved initial neonatal outcomes compared with AGA infants (adjusted odds ratio [aOR], 0.44; 95% confidence interval [CI], 0.28–0.71; p = 0.001).Conclusion Among infants delivered following PPROM, those who were LGA at delivery had improved composite adverse neonatal outcomes. SGA increases the risk of severe neonatal morbidity, early childhood death, and moderate/severe cerebral palsy at age 2.
Keywords: small for gestational age; large for gestational age; preterm premature rupture of membranes; neonatal morbidity; childhood morbidity